Assessment of complementary feeding of Canadian infants: effects on microbiome & oxidative stress, a randomized controlled trial. Issue 1 (December 2017) - Qasem, Wafaa; Azad, Meghan; Hossain, Zakir; Azad, Elnaz; Jorgensen, Sarah; Castillo San Juan, Sandra; Cai, Chenxi; Khafipour, Ehsan; Beta, Trust; Roberts, L.; Friel, James
Abstract Background The World Health Organization recommends exclusive breastfeeding until 6 months followed by introduction of iron-rich complementary foods (CFs). The aim of this study was to determine the impact of different iron-rich CFs on infant gut inflammation and microbiota. Methods Eighty-seven exclusively breastfed infants were randomly assigned to receive one of the following as their first CF: iron-fortified cereal (Cer), iron-fortified cereal with fruit (Cer + Fr), or meat (M). Urine and stool samples were collected to assess reactive oxygen species (ROS) generation, gut microbiota and inflammation. Results Fecal iron differed across feeding groups (p < 0.001); levels were highest in the Cer group and lowest in M group. A significant increase of fecal ROS formation (p < 0.002) after the introduction of CFs was observed, but did not differ across feeding groups. Fecal calprotectin increased within all groups after the introduction of CFs (p = 0.004). Gut microbiota richness increased after introduction of M or Cer + Fr. Regardless of feeding group, Coriobacteriaceae were positively correlated with ROS and Staphylococcaceae were negatively correlated with calprotectin. Conclusions Choice of first CF may influence gut inflammation and microbiota, potentially due to variations in iron absorption from different foods. Further research is warranted to fully characterize these associations and to establish implications for infant health. This study was registered in the ClinicalTrial.gov registry (Identifier No.NCT01790542 ). Trial registration This study was registered in the ClinicalTrial.gov registry under the name "Assessment of Complementary Feeding of Canadian Infants" (Identifier No.NCT01790542 ) February 6, 2013.